Answer:
The required expression is [tex]7t^2+3t+6[/tex].
Step-by-step explanation:
The function a(t) represents the cost of manufacturing product A, in hundreds of dollars, and the function b(t) represents the cost of manufacturing product B, in hundreds of dollars.
[tex]a(t)=5t+2[/tex]
[tex]b(t)=7t^2-2t+4[/tex]
The total cost of manufacturing both products is
[tex]a(t)+b(t)=5t+2+7t^2-2t+4[/tex]
Combine like terms.
[tex]a(t)+b(t)=7t^2+(5t-2t)+(2+4)[/tex]
[tex]a(t)+b(t)=7t^2+3t+6[/tex]
Therefore the required expression is [tex]7t^2+3t+6[/tex].